Comparative Study of Pre-Extraction Treatments and Buffer Modifications for Macroalgal Lectin Extraction - Fajarningsih, Nurrahmi Dewi; Nursid, Muhammad; Nugroho, Hartanto; Nuringtyas, Tri Rini; Isnansetyo, Alim (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2023)
Getting an efficient extraction approach is a crucial step in bioactive protein research, particularly lectin. This research aimed to examine the efficiency of cryogenic-grinding (CG) and freeze-dried-grinding (FG) pre-extraction treatments, and also the incorporation of phenylmethylsulphonyl fluoride (PMSF), Tween 80, polyvinylpolypyrrolidone (PVPP), 70% Ethanol (EtOH), or combination of the chemicals in the 20 mM phosphate buffered saline pH 7 (PBS) for extracting lectin from Ulva lactuca, Sargassum polycystum, and Hydropuntia edulis. The lectin content of the extracts was determined using the hemagglutination activity (HA) assay. The phenolic content was measured to determine its impact on the lectins’ HA. Lectin extraction efficiency was determined by analyzing the extracts’ minimum agglutination concentration (MAC) and total hemagglutination activity (THA). CG pre-extraction treatment produced slightly higher THA than FG, making it slightly more efficient. The EtOH treatment efficiently extracted lectin from U. lactuca and H. edulis by substantially reducing the polyphenol (PPs) content, lowering the MAC, and increasing the THA. The EtOH treatment significantly decreased the PPs and HA of the S. polycystum, suggesting that the HA is most likely produced by the PPs rather than the lectin content. Tween 80 raised the THA of U. lactuca by 17-fold with native rabbit erythrocyte compared to the control but did not affect the THA of H. edulis and S. polycystum. Several different effects of chemicals incorporated in the extraction buffers suggested that the optimum macroalgal lectin extraction strategy is species-dependent.